Pengaruh Beban Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Tri Adi Bersama (Anteraja) Staging Store Kelurahan Buaran, Kecamatan Serpong, Kota Tangerang Selatan - Fadlan Ariya Gani; Udin Saprudin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. The purpose of this study was to determine the effect of workload and compensation on employee performance at PT Tri Adi Bersama (AnterAja) Staging Store Buaran Village, Serpong District, South Tangerang City. The method used was quantitative. The sampling technique used saturated sampling, totaling 53 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination, and hypothesis testing. The results of this study are Workload has a significant effect on employee performance with a coefficient of determination value of 53.7% and hypothesis testing obtained t count > t table or (7.687 > 2.009). Compensation has a significant effect on employee performance with a coefficient of determination value of 72.5% and hypothesis testing obtained t count > t table or (11.588 > 2.009). Workload and compensation simultaneously have a significant effect on employee performance with the regression equation Y = 12.084 - 0.260X1 + 0.901X2. The coefficient of determination value is 76.8% while the remaining 23.2% is influenced by other factors. Hypothesis testing obtained F count > F table or (82.623 > 3.18)